Public Symbol in Private Contract: A Case Study - Anna Gelpern; Mitu Gulati (Washington University Law Review, 2006)
This Article revisits a recent shift in standard form sovereign bond contracts to promote collective action among creditors. Major press outlets welcomed the shift as a milestone in fighting financial crises that threatened the global economy. Officials said it was a triumph of market forces. We turned to it for insights into contract change and crisis management. This article is based on our work in the sovereign debt community, including over 100 interviews with investors, lawyers, economists, and government officials. Despite the publicity surrounding contract reform, in private few participants described the substantive change as an effective response to financial crises; many said it was simply unimportant. They explained their own participation in the shift as a mix of symbolic gesture and political maneuver, designed to achieve goals apart from solving the technical problems for which the new contract terms offered a fix. Contract terms were adopted for what they said, instead of or in addition to what they did.
Keywords: External debts -- Developing countries; Public contracts (International law); Standardized terms of contract; Contract theory